Pemodelan Digital Hospital untuk Peningkatan Mutu Layanan Tenaga Medis RS Mutiara Hati (Coopetition : Jurnal Ilmiah Manajemen, 2024)
Digital hospital is a leading concept that has been invested by developed countries in recent years. One of the hospitals that has started using the concept is Subang Mutiara Hati Hospital. The aim of this research to examine the digital hospital modeling implementation of improving the medical personnel quality services at Subang Mutiara Hati Hospital. This research used mixed methods with concurrent triangulation design consisting interview, observation, documentation & questionnaire technique. The samples were 46 informants & 46 respondents. The results showed that the digital hospital modeling at Subang Mutiara Hati Hospital had been running well & based on HIS (Hospital Information System) which consisted of non-medical & medical. HIMSS EMRAM digital hospital stage & criteria showed that Subang Mutiara Hati Hospital was appropriate at stage 1 with appropriate category (274), and was heading to stages 2, 3, and 4. Digital hospital modeling had improved the medical personnel services quality in all its dimensions which include: patient safety, effectiveness, patient-centeredness, punctuality, efficiency & equity with all categories were good score. In addition, digital hospital modeling provided many advantages, including paperless, faster service, providing convenience for medical personnel and patients, reducing human error, more secure data storage, accurate information & data.